Medicine in Ancient Mesopotamia - Supady, Jerzy (Health Promotion & Physical Activity, 2019)
The beginnings of the history of Mesopotamia date back to the mid second millennium before Christ. Various peoples settled down in that region and created more or less stable state organisms which, as the centauries passed, demonstrated and shared common cultural and civilizational heritage. Amongst the nations which made an enormous contribution to the development of medicine in Mesopotamia are Babylonians and Assyrians. The evidence of their achievements in medicine is found in the Code of Hammurabi and on clay tablets covered by cuneiform which were discovered in Nippur. In those days medicine was mainly of magical nature.